Inhibition of transcription factor T‐cell factor 3 (TCF3) using the oligodeoxynucleotide strategy increases embryonic stem cell stemness: possible application in regenerative medicine. (22nd May 2019) - Johari, Behrooz; Asadi, Zoleykha; Rismani, Elham; Maghsood, Faezeh; Sheikh Rezaei, Zahra; Farahani, Sima; Madanchi, Hamid; Kadivar, Mehdi
Abstract: The transcription factor T‐cell factor 3 (TCF3), one component of the Wnt pathway, is known as a cell‐intrinsic inhibitor of many pluripotency genes in embryonic stem cells (ESCs) that influences the balance between pluripotency and differentiation. In this study, the effects of inhibition of TCF3 transcription factor on the stemness of mouse ESCs (mESCs) were investigated using the decoy oligodeoxynucleotides (ODNs) strategy. The TCF3 decoy and its scramble ODNs were designed and synthesized. The interaction specificity of the TCF3 decoy with the TCF3 transcription factor was evaluated by the electrophoretic mobility shift assay. Subcellular localization was carried out using fluorescence and confocal microscopy. Self‐renewal and pluripotency of mESCs were analyzed by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT), cell cycle and apoptosis, alkaline phosphatase (ALP), embryoid body (EB) formation, and real‐time assays. All experiments were performed in triplicate. The results showed that knockdown of TCF3 by decoy ODNs transfection in mESCs led to an increase in the cell proliferation, ALP enzyme activity, and master regulatory stemness genes and a decrease in the number and diameter of EBs. These results supported TCF3 as a potential target to maintain the pluripotency and self‐renewal capacity of mESCs. Knockdown of the TCF3 transcription factor using decoy ODNs can be a promising method to maintain the stemness of stem cells in regenerative medicine and cell therapy researches.